Are loline alkaloid levels regulated in grass endophytes by gene expression or substrate availability? - Zhang, Dong-Xiu (Landes Bioscience, 2010)
Many cool-season grasses (Poaceae, subfam. Pooideae) possess seed-borne fungal symbionts, the epichloae, known for their bioprotective properties and especially for production of anti-insect alkaloids such as lolines. Asexual epichloae (Neotyphodium species) are primarily or entirely transmitted vertically, whereas the sexual structures (stromata) of the related Epichloä species give rise to horizontally transmissible spores (ascospores). In certain grass-Neotyphodium species symbiota, levels of lolines are extremely high and apparently limited by availability of precursor amino acids, whereas sexual epichloae generally produce much lower levels. This may reflect the inherent conflict between the vertical and horizontal transmission; although the plant and seeds may be protected by the alkaloids, the sexual cycle depends on anthomyiid flies for cross-fertilization. Given this insect role, we predicted that loline biosynthesis would be down-regulated in the stromata relative to the corresponding asymptomatic tissues (inflorescences) of the same symbiota. This prediction was substantiated, and RNA-seq and RT-qPCR analysis indicated that the loline biosynthesis genes are dramatically upregulated in asymptomatic inflorescences compared to stromata. The fundamental difference between asexual and sexual epichloae in regulation of loline alkaloid levels is in keeping with evolutionary trends for greater host control on metabolism of their vertically transmitted symbionts compared to contagious symbionts.